A Study on Social Intelligence of Post-Graduate students of MSSV, Nagaon Town of Assam. - Bibek Gope, Rashmita Roy (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
Social Intelligence is more crucial in today’s life style . It helps us to manage our life, relations with others and achieving success in our life. The present study was conducted to know the social intelligence of male and female post-graduate students of MSSV, Nagaon Town of Assam. For this purpose, descriptive survey method was used. 11 male and 19 female post-graduate students were selected for the sample by adopting stratified disproportionate random sampling technique. The data was analyzed by using ‘t’ test. The result found that 1) the post-graduate students of MSSV, Nagaon Town of Assam have scored high level of social intelligence. 2) there is no significant difference in social intelligence between male and female post-graduate students of MSSV, Nagaon Town of Assam and for third objective it was found that 3) significant difference in social intelligence between 1st semester and 3rd semester post-graduate students of MSSV. Nagaon Town of Assam and so on.